1999
DOI: 10.1159/000030050
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mouse Mammary Adenocarcinoma (EMT6) Growth and Metastases in Mice by a Modified Form of C-Reactive Protein

Abstract: Mice were injected in the hind limb with a mouse mammary adenocarcinoma cell line, EMT6, and tumor growth at the primary site as well as the incidence of lung metastases were measured. Groups of animals were treated with the acute-phase reactant C-reactive protein, (native-CRP), or a conformationally modified form of CRP (mCRP) made by dissociating CRP subunits under chelating, denaturing conditions. Each form of CRP was injected (intravenously) through the tail vein, encapsulated in large unilamellar lipid ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Concern has been addressed through the use of heterologous systems. 27 Exposing mice to huge 28 reported that when mice were injected with 100 g IV (Ϸ5 mg/kg) of mCRP, little or no mCRP was detected in a number of serum specimens. Because mCRP is hydrophobic and thus tends to self-aggregate, its movement away from the injection site as a free protein is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Concern has been addressed through the use of heterologous systems. 27 Exposing mice to huge 28 reported that when mice were injected with 100 g IV (Ϸ5 mg/kg) of mCRP, little or no mCRP was detected in a number of serum specimens. Because mCRP is hydrophobic and thus tends to self-aggregate, its movement away from the injection site as a free protein is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…mCRP binds to a number of different ligands to CRP and also exhibits a different set of biologic activities. More recently, it has been shown that mCRP has profound inhibitory effects on tumor growth and metastatic ability of an adenocarcinoma in mice (Kresl et al, 1999). Cross-reactive epitopes of mCRP have also been detected in the fibrous elements of blood vessels and lymphatic organs suggesting that mCRP may be present in extracellular spaces (Samberg et al, 1988).…”
Section: Crpmentioning
confidence: 99%
“…In 1983, Potempa et al found that under certain conditions, CRP may dissociate into monomers (32). The monomeric CRP was found to contribute in vivo (33,34) and to have extensive physiological roles either in vitro (35)(36)(37) or in vivo (38), indicating the factuality and stability of such kind of structural form of CRP. It is believed that the exposure of the new epitope of each monomer (neo-antigen) leads to some of the new physiological roles of monomeric CRP (39).…”
Section: The Physiological Significance Of the Dissociation Of Hcrp Smentioning
confidence: 99%